Auctions and leaks: A theoretical and experimental investigation - Sven Fischer; Werner Güth; Todd R. Kaplan; Ro'i Zultan (Friedrich Schiller University Jena, 2017)
In first- and second-price private value auctions with sequential bidding, second movers may discover the first movers' bid. Equilibrium behavior in the first-price auction is mostly unaffected but there are multiple equilibria in the second- price auction. Consequently, comparative statics across price rules are equivocal. Experimentally, leaks in the first- price auction favor second movers but harm first movers and sellers, as theoretically predicted. Low to medium leak probabilities eliminate the usual revenue dominance of first- over second-price auctions. With a high leak probability, second-price auctions generate significantly more revenue.
Keywords: C72; C91; D44; 330; auction; collusion; espionage; laboratory experiment